Skill performance in Cardiopulmonary Resuscitation among Laypersons and health care professionals - Chin, Su Na (2016)
Cardiopulmonary resuscitation (CPR) is the key determinant for survival from out-of-hospital cardiac arrest. The skill and ability of the rescuer to perform quality CPR are important to assure the success or failure of survival. This study aims to explore the differences and factors that affect performance of CPR skills, by taking into account demographic variations between the Health Care Professionals (HCP) and laypersons. A total of 144 responders were interviewed using a self-administered questionnaire and a skill evaluation checklist by two qualified instructors. HCP and laypersons groups report comparable skill retention in CPR but HCP shows better basic life support (BLS) knowledge. Results suggest female HCP has better BLS knowledge compared to male HCP and time length after first BLS course contributes to significant difference in BLS knowledge among laypersons. Laypersons who had attended refresher course have better CPR skill rentention compared to those who had not.